Energy Optimization For Wireless Video Transmission Employing Hybrid ARQ - Zhang, Bentao; Cosman, Pamela; Milstein, Laurence B. (IEEE transactions on vehicular technology, 2019)
In this paper we investigate energy-optimized wireless video transmission employing a hybrid automatic repeat request. We formulate the problem as maximizing the video quality, subject to a constraint on the wireless transmission energy consumption. We consider multiple parameters in multiple layers in a wireless video transmission system: transmit power, alphabet size, FEC code rate, maximum number of transmissions, and unequal video data importance. An analytical framework is proposed to include these parameters, which allows us to divide this problem into two sub-problems: data transmission and unequal error protection. The problem is tackled by solving the two sub-problems, which are done by exhaustive search and convex optimization, respectively. Simulations of different videos show that the proposed scheme outperforms methods using conventional data transmission and/or unequal error protection.